Link Between the Dynamics of Granular Flows and the Generated Seismic Signal: Insights From Laboratory Experiments. Issue 6 (21st June 2018) - Farin, Maxime; Mangeney, Anne; de Rosny, Julien; Toussaint, Renaud; Trinh, Phuong‐Thu
Abstract : Granular column collapse experiments have been conducted on a flat rough surface tilted at various angles with synchronous measurements of the flow dynamics and the emitted seismic signal. Our results show that the ratio of radiated seismic energy to potential energy lost by the granular flows decreases slightly from 0.033% to 0.017% with increasing slope angle on a poly(methyl methacrylate) (acrylic) plate. This is about 90 times lower than for the impact of a single particle of the same diameter. The experimental granular flows generated signals with frequencies lower than 20 kHz, with a mean value around 5 kHz, which are shown to be similar to the frequencies emitted by a single‐particle impact. The rise phase and maxima of the amplitude and frequencies of the seismic signals generated by our experimental granular flows are mostly controlled by flow motion in the direction normal to the slope, while their decay phase depends on downslope particle speeds. The granular flow regime changes from dense to more agitated flows above a critical slope angle that is about half the friction angle of the granular material. This change is reflected in (1) the shape of the temporal variation of the seismic amplitude and frequencies, with a decay phase lasting much longer and (2) the shape of the cumulative radiated seismic energy, which changes above the same critical slope angle. Implications of these results for the interpretation of seismic emissions from experimental and natural granular flows are discussed. Key Points: We compare the dynamics and the generated seismic signal of experimental granular flows on a rough plane inclined at various angles Granular flow seismic efficiency decreases as the slope angle increases and is about 90 times lower than for the impact of a single grain The shape of the seismic signal changes after a critical slope angle because the flow regime changes from a dense to a more agitated flow